EFEKTIVITAS GREEN FINANCE PADA PEMBIAYAAN BERKELANJUTAN DI DESA PEMATANG SERAI - Sari, Wahyu Indah; Sugiarto, Abdi; Nasution, Lia Nazliana; Ningsih, Resti Triana (ITB AAS Indonesia Surakarta, 2024)
This study is to analyze the effectiveness of green financing in sustainable financing for home industry players in Pematang Serai Village. Green financing is a financing scheme or lending to business actors that is environmentally friendly. Based on Government regulations to be able to receive financing with a green financing scheme. To achieve industrial, social and economic advantages to reduce the threat of global warming and prevent other environmental and social problems, the goal is to shift the goal to a competitive low-carbon economy, so that it can strategically promote environmental investment in various areas of business/economy. The research data is sourced from the results of interviews with industrial homes in Pematang Serai Village, Tanjung Pura District, Langkat Regency, North Sumatra Province. as borrowers/customers of the Green Financing Program with the help of questionnaires so that the questions in the interview are more systematic. Sampling was carried out using proportionate random sampling technique. The data analysis used was: Descriptive Statistical Analysis and Multiple Linear Regression. The results of the study explained that green credit partially did not have a significant effect on green finance in Pematang Serai Village, Tanjung Pura District, Langkat Regency, while green product innovation and green technology partially had a significant effect on green finance in Pematang Serai Village, Pematang Serai Village, Tanjung Pura District, Langkat Regency.